The History and Architecture of the Asal Penampaan Mosque in Penampaan Village, Blangkejeren District, Gayo Lues Regency - Ismi, Muhamad; Rohani, Laila (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
This article delves into the history and architecture of the Penampaan Mosque situated in Penampaan Village, Blangkejeren Subdistrict, Gayo Lues Regency. The Penampaan Asal Mosque, located in Penampaan Village, Blangkejeren District, Gayo Lues Regency, stands as a testament to the rich cultural heritage and religious ethos of the local populace. Established in 815 AH/1412 AD, the mosque boasts unique traditional architecture, featuring walls crafted from a blend of soil and husks, and roofs adorned with nipah leaves, symbolizing serenity, and elegance. Serving as a hub for religious and communal gatherings, the Penampaan Asal Mosque has been a witness to the Islamic journey in the Gayo Lues region. Its enduring presence underscores the significance of safeguarding cultural legacies and religious principles. This study contributes to the understanding of local history and architectural heritage preservation efforts.